The role of women as goddesses in the archaeological sites of South Kurdistan - Syed, Zhino Abdullah; Abdulsamad, Dr. Rafda Abdullah (Sulaimani Journal for Humanities, 2026)
Women have always played an important role in different fields of human society. One of the roles is to depict them as goddesses, of course, on many archaeological remains in South Kurdistan, including carvings of mountains and seals, etc., or mentioning them in historical texts. Sometimes these goddesses had temples in big cities and the temple was their main center of worship. Of course, these goddesses had their own symbols and some of them were not only gods of one field but also several different purposes With the purpose and reasons for their worship in different parts of South Kurdistan during the archaeological discoveries and their appearance on archaeological remains.